Narrative nursing as a holistic approach in modern healthcare: Integrating emotional and physical care - Yildiz, Guzel Nur; Ciftci, Bahar (Baishideng Publishing Group Inc, 2025)
Narrative nursing (NN) is emerging as a critical approach in modern healthcare, addressing the complex interplay between psychological well-being and physical recovery. This manuscript discusses a study on NN and its role in alleviating psychological distress in patients with acute pancreatitis, published in the World Journal of Psychiatry. Their research demonstrates that NN, through structured storytelling, significantly reduces anxiety and depression, thereby enhancing patient satisfaction and fostering emotional resilience. This therapeutic approach extends beyond symptom management, offering a comprehensive strategy that supports the mental and emotional recovery of patients facing severe health challenges. NN provides a unique framework for engaging patients in their care journey, promoting a sense of agency, and strengthening the patient-provider relationship. In this manuscript, we explore the broader implications of NN by synthesizing findings from various studies, showing that NN is effective not only in acute settings but also in oncology, chronic illness management, and palliative care. The evidence indicates that integrating NN into standard clinical practice could enhance healthcare outcomes by addressing the holistic needs of patients, supporting psychological resilience, and fostering a compassionate healthcare environment.
Keywords: Narrative nursing; Patient-centered care; Psychological distress; Emotional resilience; Holistic recovery; Structured storytelling